SPEAKING THROUGH CRISIS: ANALYSING LEADERSHIP ATTRIBUTES IN KHAIRY JAMALUDDIN’S COVID-19 UPDATES - Azmi, Azzieatul Syazwanie; Aziz, Anis Idayu; Salleh, Salwani Mohd; Abidin, Nazatul Shahreen Zainal (Cirebon International Conference on Education and Economics Proceeding, 2025)
The COVID-19 pandemic has brought global political leadership into sharp focus, highlighting how national leaders’ policy and communication choices directly impact the effectiveness of crisis response. While extensive research has explored the political dynamics of leadership (Haslam et al., 2021), less attention has been given to the specific attributes that enable leaders to communicate effectively with the public during a global crisis. This study aims to examine the leadership attributes demonstrated by Khairy Jamaluddin in his COVID-19 daily update press conferences. Using discourse analysis and a qualitative approach, the study analyses three press conference videos to understand how he constructed and conveyed his leadership traits. The findings reveal that Khairy Jamaluddin consistently exhibited key leadership attributes in his speeches, which played a crucial role in fostering public trust.